Outcome of melanoma patients with elevated LDH treated with first-line targeted therapy or PD-1-based immune checkpoint inhibition. (May 2021) - Knispel, Sarah; Gassenmaier, Maximilian; Menzies, Alexander M.; Loquai, Carmen; Johnson, Douglas B.; Franklin, Cindy; Gutzmer, Ralf; Hassel, Jessica C.; Weishaupt, Carsten; Eigentler, Thomas; Schilling, Bastian; Schummer, Patrick; et al.
Abstract: Background: Elevated lactate dehydrogenase (LDH) is a known predictive and prognostic factor for a poor outcome in patients with metastatic melanoma. It is unclear whether first-line targeted therapy (TT) or immune checkpoint inhibition (ICI) is more beneficial in melanoma patients with elevated LDH because prospective studies in this area are lacking. Methods: This multicentre retrospective cohort study was conducted at 25 melanoma centres worldwide to analyse progression-free survival (PFS) and overall survival (OS) among melanoma patients with elevated LDH. The role of confounders was addressed by using inverse probability of treatment weighting. Results: Among 173 BRAF V600-mutant patients, PFS at 12 months in the TT group was 22% compared with 52% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.6, 95% CI 0.4–1.0, p = 0.07) and 18% in the anti-PD-1 monotherapy group (HR 1.8, 95% CI 1.2–2.8, p = 0.003). Twelve months' OS was 48% in the TT group compared with 83% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.5, 95% CI 0.3–1.0, p = 0.03) and 50% in the anti-PD-1 monotherapy group (HR 1.2, 95% CI 0.8–2.0, p = 0.37). The ORR in the TT group was 63%, compared with 55% and 20% in the combined anti-PD-1 and anti-CTLA-4 and anti-PD-1 monotherapy group, respectively. Among 314 patients receiving ICI first-line, PFS at 12 months was 33% in the anti-PD-1 group versus 38% in the combined anti-PD-1 and anti-CTLA-4 group (HR 0.8, 95% CI 0.6–1.0; p = 0.07). OS at 12 months was 54% in the anti-PD-1 group versus 66% in the combined ICI group (HR 0.7, 95% CI 0.5–1.0; p = 0.03). The ORR was 30% in the anti-PD-1 monotherapy group and 43% in the combined anti-PD-1 and anti-CTLA-4 group. Results from multivariate analysis confirmed the absence of qualitative confounding. Conclusions: Among BRAF -mutant patients with elevated LDH, combined anti-PD-1 and anti-CTLA-4 blockade seems to be associated with prolonged OS compared with first-line TT. Among patients receiving ICI as a first-line treatment, OS appears to be longer for the combination of anti-PD-1 and anti-CTLA-4 than for anti-PD-1 alone. Graphical abstract: Image 1 Highlights: This multicentre cohort study investigated 403 melanoma patients with elevated LDH. End-points were progression-free and overall survival (OS) in first-line therapy. Targeted therapy (TT) achieved the highest response rates in BRAF- mutant patients. OS appears longer for combined anti-PD-1 and anti-CTLA-4 than for TT. OS appears longer for combined anti-PD-1 and anti-CTLA-4 than for anti-PD-1 alone.